Green-Synthesized MgO Nanoparticles: Structural Insights and Antimicrobial Applications - Rădulescu, Denisa Maria; Neacșu, Ionela Andreea; Vasile, Bogdan Ștefan; Surdu, Vasile Adrian; Oprea, Ovidiu Cristian; Trușcă, Roxana Doina; Chircov, Cristina; Popescu, Roxana Cristina; Ilie, Cornelia Ioana; Dițu, Lia Mara; Drumea, Veronica; Andronescu, Ecaterina (MDPI, 2025)
Magnesium oxide nanoparticles, or MgO NPs, have garnered a lot of attention because of their exceptional stability, biocompatibility, and antibacterial properties. However, many of the green production methods used today have limited mechanistic knowledge and low reproducibility. In order to get over these challenges, we created a standardized and environmentally friendly process for producing MgO NPs using orange peel extract, a naturally occurring biowaste source rich in phytochemicals that acts as a stabilizing and reducing agent. Active precursor alteration during synthesis was clearly shown by X-ray diffraction (XRD) and thermal analysis (TGA-FTIR), while imaging techniques showed extremely crystalline cubic-phase MgO nanoparticles that were about 9 nm in size. The NPs displayed an irregular shape between 10 and 40 nm and a positive surface charge of +11.74 mV. Terpenoids, polymethoxyflavones, fatty acids, and sugars all work in collaboration with direct nucleation, regulate particle growth, and stabilize the nanoparticles, according to GC-MS analysis. The MgO NPs showed remarkable cytocompatibility in biology, preserving >80% viability in fibroblast and osteoblast cell lines while causing distinct metabolic regulation in osteoblasts without changing the shape of the cells. Consistent moderate activity against a variety of pathogens was confirmed by antimicrobial and antibiofilm assays, with special effectiveness against Gram-positive bacteria and Pseudomonas aeruginosa biofilms. This study shows that these MgO NPs have good biocompatibility and antimicrobial qualities, indicating the need for more research for possible biomedical applications. It also clarifies the molecular role of phytochemicals in nanoparticle formation and provides a repeatable green synthesis pathway.
Keywords: green synthesis; magnesium oxide nanoparticles; orange peel extract; phytochemical synergy; biocompatibility; antimicrobial activity; antibiofilm